The standard of proof of «probability of evidence» in commercial proceedings of Ukraine - Verbitska , Mariana; Prysiazhniuk , Mariana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article is devoted to the study of the standards of proof in Commercial litigation. Attention is focused on the impact of the evaluation of evidence from the position of removing the concept of «sufficiency» and establishing the concept of «probability» in the Commercial process in connection with changes in the Commercial Procedural Code of Ukraine in accordance with the Law of Ukraine dated September 20, 2019 «On Amendments to Certain Legislative Acts» of Ukraine regarding stimulation of investment activities in Ukraine. The authors analyze the activity of the court in the evaluation of evidence and the application of the standards of proof in conducting such an evaluation. The article compares the standard of proof and the standard of probability of evidence, examines the reasons and motives for replacing the standard of proof with the standard of probability of evidence. In the course of writing the publication, the authors touch on the practical aspects of applying the standards of proof, analyze judicial practice, in particular, the positions of the Supreme Court on this matter. It was established that, according to the intention of the legislator, the introduction of changes, namely in the category «probability of evidence», was supposed to contribute to increasing the efficiency of the commercial court in rendering decisions based on new approaches to the evaluation of evidence in a case with the aim of adopting a fair, impartial and legal resolution of disputes, and as well as ensuring quality protection of violated, unrecognized or contested rights and legitimate interests of individuals and legal entities, the state. The result of the research is the outline of certain problematic issues related to the implementation of the "probability of evidence" standard in the economic process and the clarification of the expediency of such an innovation, in particular, the position expressed that the declaration in Article 79 of the Civil Code of Ukraine of the «probability of evidence» standard in practice did not lead to any changes in the commercial court’s approaches to evaluating evidence.